2013
DOI: 10.1021/ma4005549
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Living trans-1,4-Polymerization of Isoprene by Cationic Rare Earth Metal Alkyl Species Bearing a Chiral (S,S)-Bis(oxazolinylphenyl)amido Ligand

Abstract: A series of chiral mononuclear dialkyl complexes [(S,S)-BOPA]Ln(CH2SiMe3)2 (1, 2) (BOPA = (S,S)-bis(oxazolinylphenyl)amido; Ln = Sc (1); Ln = Lu (2)) and binuclear alkyl complexes [ο-(S)-OPA–C6H4–(CH2SiMe3)CN–CH( i Pr)CH2–O]Ln(CH2SiMe3)}2 (3, 4) (OPA = (oxazolinylphenyl)amine; Ln = Y (3); Ln = Tm (4)) have been synthesized in moderate yields via one-pot acid–base reactions by use of the tris(trimethylsilylmethyl) rare earth metal complexes with the chiral tridentate (S,S)-bis(oxazolinylphenyl)a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 61 publications
(10 reference statements)
5
55
1
Order By: Relevance
“…In the exploration process of amido metal complexes, their catalytic polymerization properties have been extensively studied after the report of SHOP type catalysts. [6] Hou et al reported on the polymerization of isoprene by using cationic [PNP] type amido rare-earth-metal pincer complexes. [7] Liang and coworkers also reported the catalytic polymerization application of [PNP] type amido aluminum pincer complexes in the presence of B(C 6 F 5 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the exploration process of amido metal complexes, their catalytic polymerization properties have been extensively studied after the report of SHOP type catalysts. [6] Hou et al reported on the polymerization of isoprene by using cationic [PNP] type amido rare-earth-metal pincer complexes. [7] Liang and coworkers also reported the catalytic polymerization application of [PNP] type amido aluminum pincer complexes in the presence of B(C 6 F 5 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The acid–base reaction between the rare earth metal trialkyl complex Ln(CH 2 SiMe 3 ) 3 (THF) 2 and the (S,S)‐bis(oxazolinylphenyl)amine ligand in toluene at 25 °C afforded the chiral C 2 ‐symmetric (S,S)‐bis(oxazolinylphenyl)amido rare earth metal dialkyl complexes [(S,S)‐BOPA]Ln(CH 2 SiMe 3 ) 2 ( 6a , 6b ) ( 6a : Ln = Sc; 6b : Ln = Lu) in high yields, which are soluble in common organic solvents such as THF, toluene, and hexane [Fig. (e)].…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, we reported the first cationic chiral rare earth alkyl catalyst for the living trans ‐1,4‐polymerization of isoprene [Fig. (c)] . Activated by activator such as borate [Ph 3 C][B(C 6 F 5 ) 4 ], the scandium and lutetium dialkyl complexes 6a and 6b showed highly catalytic activity (up to 2.0 × 10 5 g/mol Ln h) and complete trans ‐1,4‐selectivity for the living polymerization of isoprene to afford the pure trans ‐1,4‐PIP ( trans ‐1,4‐selectivity: 100%) with the narrow molecular weight distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang, Li and co‐workers have demonstrated that the i Pr‐BOPA protio‐ligand reacts with the organometallic precursors [Ln(CH 2 SiMe 3 ) 3 (THF) 2 ] (Ln = Sc, Y, Lu, Tm). Whilst rare‐earth elements with larger ionic radii (Y and Tm) underwent ring‐opening of the oxazoline rings, those with smaller ionic radii (Sc and Lu) formed well‐defined stable complexes that were active in the polymerisation of isoprene . We sought to extend the knowledge‐base of analogous organometallic complexes by using the full range of BOPA ligand derivatives included in this article, but bearing the alternative alkyl ligand, CH 2 SiMe 2 Ph.…”
Section: Resultsmentioning
confidence: 99%